Pengaruh Gaya Kepemimpinan Transformasional Terhadap Motivasi Kerja dan Kinerja Pegawai pada Badan Kepegawaian Daerah Provinsi Sulawesi Tenggara (Indo-Fintech Intellectuals: Journal of Economics and Business, 2024)
Human resources in an organization are very important capital to achieve the vision, mission, and goals of the organization. Especially at the Regional Staffing Agency of Southeast Sulawesi Province, competent human resources are needed to improve employee performance and staffing services. However, there is still a knowledge gap about the effect of transformational leadership style on work motivation and employee performance. This study used a qualitative method with an explanatory design with a sample of 89 employees of the Regional Staffing Agency of Southeast Sulawesi Province. The main results showed that transformational leadership style has a positive and significant effect on work motivation and employee performance. Increased work motivation also has a positive effect on employee performance. Transformational leadership style mediated by work motivation makes a significant contribution to improving employee performance. This study implies that the application of transformational leadership style can increase work motivation and employee performance at the Regional Staffing Agency of Southeast Sulawesi Province, to provide more optimal staffing services